ANALISIS KADAR VITAMIN C PADA MINUMAN PROBIOTIK BUAH BLIGO (Benincasa hispida) - Patty, Rezza Julian; Watuguly, Theopilus W; Tuapattinaya, Prelly M (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: Bligo (Benincasa hispida) is a Creeper plant, wooden trunk, soft, hairy and green. Bligo (Benincasahispida) contains water, protein, vegetable fats, carbohydrates, fiber, minerals and vitamins. Probiotic drinks are lacticacid fermented drinks that contain lactic acid bacteria and can provide health effects when consumed. Vitamin C isknown as ascorbic acid (C6H8O6), it is one of the vitamins needed by the body and its functions to increase the body'simmune system. The Measurement of vitamin C in probiotic drinks used spectrophotometric tool.Methods: This study used a qualitative descriptive research and the aim to determine the amount of vitamin C levelsin a probiotic drink made from Bligo (Benincasa hispida).Results: Based on the results of conducting this research, probiotic drinks containing Vitamin C in sample 1 with avitamin C in the level of 0.00790 and samples 2 and 3 with a vitamin C in the level of 0.00869%.Conclusion : Probiotic drink contains vitamin C in samples 2 and 3 with a Vitamin C level of 0.00869%. So Bligo(Benincasa hispida) can be used as a probiotic drink because it contains vitamin C.